DNA Barcoding Identifies Endangered Sharks in Pet Food Sold in Singapore - French, Ian; Wainwright, Benjamin J. (Frontiers in Marine Science, 2022)
Shark populations have declined by more than 70 % over the past 50 years, these declines have largely been attributed to increases in fishing effort. Despite increased public awareness surrounding the conservation of sharks, three quarters of all oceanic shark species are currently considered at risk of extinction. Here, we use DNA barcoding to identify shark DNA found in pet food purchased within Singapore. We identified a number of sharks that have some degree of control over their trade exerted under the auspices of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), or through their classification as threatened by the International Union for Conservation of Nature (IUCN). The most commonly identified shark was the blue shark, Prionace glauca, a species that is not CITES listed, or classified as threatened by the IUCN, but one which scientific evidence suggests is overexploited and should have its catch regulated. The second most commonly encountered species was the CITES Appendix II listed silky shark, Carcharhinus falciformis. None of the products specifically listed shark as an ingredient, listing only generic terms such as “ocean fish”, “white fish” or “white bait” etc. The vague terminology used to describe pet food ingredients, and in some cases the mislabelling of contents, prevents consumers - in this case pet owners - from making informed and environmentally conscious decisions, consequently, pet owners and animal lovers may unwittingly be contributing to the overfishing of endangered sharks.